The Influence of Multiculturalism-Based Character Education on the Personality Development of Students at PGRI Silampari University - Susilo, Agus; Sukenda Egok, Asep; Dwinanda, Krisnaldi; Widyaningrum, Fitriyan Della (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to examine the influence of multiculturalism-based character education on the personality development of students at Universitas PGRI Silampari. Multiculturalism-based character education is an approach that integrates the values of cultural diversity, tolerance, and respect for differences into the learning process. This study employs a quantitative method using a survey technique involving several students as respondents. The results of the research indicate a significant positive influence of multiculturalism-based character education on students' personality development. Students engaged in multiculturalism-based character education showed improvements in aspects of tolerance, respect for differences, and the strengthening of an inclusive self-identity. These findings highlight the importance of implementing character education that emphasizes multiculturalism in order to foster more holistic and adaptive personalities in students in the context of social diversity.